A low-angle brittle shear zone in the western Sør Rondane Mountains, Dronning Maud Land, East Antarctica — Implication for assembly of Gondwanaland. (November 2017) - Tsukada, Kazuhiro; Yuhara, Masaki; Owada, Masaaki; Shimura, Toshiaki; Kamei, Atsushi; Kouchi, Yoshikazu; Yamamoto, Koshi
Graphical abstract: Abstract: The Sør Rondane Mountains (SRM), East Antarctica, lie within the late Neoproterozoic–early Paleozoic collision zone related to the formation of the Gondwana supercontinent. Many studies have been carried out in the eastern SRM, whereas fundamental questions on the western SRM remain unanswered, e.g. detail metamorphic history, age, kinematics of sheared rocks and others. This paper describes lithology and structure of the western SRM, and the tectonic implications of a low-angle brittle shear zone within this area, the Kanino-tume Shear Zone (KSZ), is discussed. Rocks of the study area are divided into units 1–3 based on their lithology and structural position. Units 1 and 2 are composed mainly of Neoproterozoic gneiss, and unit 3 consists mainly of ca. 1000–800 Ma metatonalite. Units 2 and 3, both separated by a mylonite/ultramylonite zone formed by dextral shearing (Main Shear Zone: MSZ), tectonically overlie unit 1 with the KSZ. The KSZ, showing top-to-the south sense of shear, cuts MSZ (∼  ca . 530 Ma) and is intruded by mafic dikes ( ca. 560–440 Ma). Therefore, units 2 and 3, which had been juxtaposed by the dextral movement along the MSZ, rode together onto unit 1 along the KSZ by top-to-the southward movement at late Neoproterozoic–early Paleozoic time. The KSZ gives critical evidence for late Neoproterozoic–early Paleozoic movement in the SRM within the East African–Antarctic orogen.